Dampak Hutan Kemasyarakatan terhadap Kondisi Sosial Ekonomi Penyadap Getah Pinus di Desa Ronggur Nihuta Kecamatan Ronggur Nihuta Kabupaten Samosir - Simbolon, Ika; Iskarni, Paus (Lembaga Yasin AlSys, 2024)
This research aims to determine the impact of the potential existence of community forests on economic and social conditions in Ronggur Nihuta Village, Ronggur Nihuta District, Samosir Regency. The method used in this research is Quantitative Descriptive. The results of the research show: 1. The income level of pine sap tappers increased after pine sap tapping was Rp. 680,000,000 (46%). 2. Ownership of valuables increased after pine resin tapping, namely motorbikes, increased by 2, previously 32(80%), to 35(88%). 3. Ownership status of the house occupied is almost all owned by yourself (85%), the cost of renovating the previous house was IDR 680,000 (18%) to IDR 3,030,000 (82%). 4. The child's current education is high school (70%). Previous education costs were IDR 80,250,000 (46%) to IDR 91,250,000 (54%). 5. The health condition of the pine sap tapper is good in work activities (90%), the cost of medical treatment for family members was previously IDR 20,292,000 (48%) to IDR. 22,814,000 (52%).